Carbon black masterbatch and wet mixing preparation method thereof and rubber product

In the wet kneading process, the latex and carbon black are modified by using vinyl-containing pyridine monomer and maleic anhydride, and metal coordination bonds and hydrogen bonds are formed, the problem of insufficient hardness and fixed extension stress of carbon black masterbatch products in the wet kneading process is solved, and the performance of rubber products is significantly improved.

CN118909332BActive Publication Date: 2025-03-25QINGDAO HEIMAO NEW MATERIAL RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410854701.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-03-25
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

The rubber products containing carbon black masterblock prepared by wet kneading process have insufficient fixed extension stress and hardness, which cannot meet the application requirements of rubber products.

Method used

A wet kneading preparation method of carbon black masterbatch is adopted. By mixing natural latex, initiator and vinyl-containing pyridine monomer, a modified latex is obtained; maleic anhydride is mixed with the carbon black solution to obtain a modified carbon black slurry; then the modified carbon black slurry is mixed with the modified latex, and a compound containing metal ions is added to form metal coordination bonds and hydrogen bonds, thereby enhancing the crosslinking degree between carbon black and latex.

Benefits of technology

The connection strength of carbon black masterbatch is improved, and the hardness and fixed extension stress of rubber products containing carbon black masterbatch is significantly improved, meeting the application requirements of rubber products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118909332B_ABST
    Figure CN118909332B_ABST
Patent Text Reader

Abstract

The present application relates to the field of rubber, and specifically discloses a carbon black masterbatch and a wet mixing preparation method thereof and a rubber product. The wet mixing preparation method of the carbon black masterbatch comprises: mixing natural latex, an initiator and a vinyl-containing pyridine monomer, stirring to obtain a modified latex; mixing maleic anhydride with a carbon black solution to obtain a modified carbon black slurry; the modified carbon black slurry is mixed with the modified latex and then coagulated and precipitated, and a compound containing metal ions is added in the process to obtain a primary product; the metal ions are used to construct metal coordination bonds, and the primary product is washed and dried to obtain the carbon black masterbatch. The yield of the carbon black masterbatch obtained by the above preparation method is high, and the hardness and tensile stress of the rubber product including the carbon black masterbatch are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of rubber, and more specifically, to a carbon black masterbatch and a wet mixing preparation method thereof and a rubber product. Background Art

[0002] Rubber is the main raw material of tires. The preparation process of rubber mainly includes dry mixing and wet mixing. Among them, dry mixing is to mix rubber raw materials, fillers (such as carbon black, white carbon black, etc.) and other solid substances such as plasticizers, antioxidants, vulcanizers, etc. in a certain proportion in an internal mixer or an open mixer according to a certain formula. Due to the disadvantages of dry mixing process such as high energy consumption, high noise, and serious dust pollution, rubber products are currently prepared through wet mixing process, that is, fillers and other additives are coagulated and precipitated with latex under liquid phase conditions to obtain the final product.

[0003] In the process of preparing rubber by wet mixing process of carbon black and latex, although the wear resistance and tensile strength of rubber can be ensured by effectively dispersing carbon black in latex, the tensile stress and hardness of the tire containing carbon black masterbatch will be significantly reduced, which does not meet the application requirements of rubber products. Summary of the invention

[0004] In order to improve the tensile stress and hardness of a rubber product containing carbon black masterbatch prepared by a wet mixing process, the present application provides a carbon black masterbatch and a wet mixing preparation method thereof and a rubber product.

[0005] In the first aspect, the present application provides a wet mixing method for preparing a carbon black masterbatch, which adopts the following technical scheme:

[0006] A wet mixing preparation method for carbon black masterbatch, comprising:

[0007] Mixing natural rubber latex, an initiator and a vinyl-containing pyridine monomer, stirring, and obtaining a modified latex;

[0008] mixing maleic anhydride with the carbon black solution to obtain a modified carbon black slurry;

[0009] The modified carbon black slurry is mixed with the modified latex and then coagulated and precipitated, and a compound containing metal ions is added in the process to obtain a primary product; the metal ions are used to construct metal coordination bonds, and the primary product is washed and dried to obtain the carbon black masterbatch.

[0010] By adopting the above technical scheme, the dry rubber in natural latex is modified by using vinyl-containing pyridine monomers, and pyridine groups can be connected to the molecular chains of the dry rubber in the latex. The pyridine groups are rigid groups, which help to improve the connection strength of the carbon black masterbatch, thereby promoting the improvement of the hardness and tensile stress of rubber products containing the carbon black masterbatch; by modifying the carbon black with maleic anhydride, carboxyl groups can be connected to the surface of the carbon black. The free carboxyl groups on the surface of the carbon black can break the stability of the dry rubber particles in the latex and demulsify the latex under the premise of avoiding the premature demulsification of the latex caused by strong acid. In other words, the carboxyl groups on the surface of the carbon black can play the role of a latex flocculant, allowing the carbon black and latex to combine more fully and completely, thereby improving the dispersion and the yield of the carbon black masterbatch.

[0011] The present application unexpectedly discovered that hydrogen bonds can be formed between the carboxyl groups on the surface of carbon black and the N atoms in the pyridine groups on the dry rubber molecular chains in the natural latex, and that the pyridine groups on the dry rubber molecular chains in the latex and the oxygen-containing functional groups on the surface of carbon black interact with metal ions to form coordination bonds. Under the synergistic effect of hydrogen bonds and coordination bonds, in the carbon black masterbatch, the degree of crosslinking between the carbon black and the dry rubber in the latex is increased, and the interaction force is enhanced, thereby effectively improving the connection strength inside the carbon black masterbatch, and further promoting the improvement of the hardness and tensile stress of rubber products containing the carbon black masterbatch.

[0012] Optionally, the preparation process of the modified latex includes at least one of the following features (a)-(d):

[0013] (a) When the solid content of the natural rubber latex is 50% to 60%, the amount of the natural rubber latex used is 160 to 200 parts by weight, the amount of the initiator used is 1 to 10 parts by weight, and the amount of the vinyl-containing pyridine monomer added is 1 to 20 parts by weight;

[0014] (b) The mixing temperature is 30 to 100°C and the mixing time is 2 to 8 hours;

[0015] (c) the initiator comprises at least one of dibenzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), tert-butyl hydroperoxide (t-BHP), cumene hydroperoxide (CHP), dicumyl peroxide (DCP), potassium persulfate, ammonium persulfate and hydrogen peroxide;

[0016] (d) The vinyl-containing pyridine monomer includes at least one of 2-vinylpyridine, 4-vinylpyridine, 2-methyl-5-enylpyridine, 2-allylpyridine and 2-(3-butenyl)pyridine.

[0017] Optionally, the preparation process of the modified carbon black slurry includes at least one of the following features (e)-(h):

[0018] (e) The carbon black solution is a mixed solution of carbon black and water with a solid content of 1% to 10%;

[0019] (f) the mass ratio of carbon black in the carbon black solution to the maleic anhydride is 100:0.1-30;

[0020] (g) the maleic anhydride and the carbon black solution are mixed for 10 to 60 minutes at a temperature of 10° C. to 100° C.;

[0021] (h) The maleic anhydride and the carbon black solution are mixed at a stirring speed of 0 to 4000 rpm.

[0022] Optionally, the metal ion is Zn 2+ , Fe 3+ Or Ga 2+ .

[0023] Optionally, the compound containing metal ions is zinc chloride.

[0024] Optionally, the mass ratio of the zinc chloride to the dry rubber in the natural rubber latex is 0.1 to 20:100.

[0025] Optionally, the mass ratio of the zinc chloride to the dry rubber in the natural rubber latex is 0.1 to 20:100.

[0026] Optionally, the primary product is dried at a temperature of 30-110°C.

[0027] In a second aspect, the present application provides a carbon black masterbatch prepared by the wet mixing preparation method of the carbon black masterbatch described in any one of the first aspects above.

[0028] In a third aspect, the present application provides a rubber product, comprising the carbon black masterbatch described in the second aspect, and also comprising zinc oxide, stearic acid, an antioxidant, an accelerator and sulfur.

[0029] The rubber products can be used to prepare tires, V-belts, conveyor belts or hoses.

[0030] In summary, this application has the following beneficial effects:

[0031] By mixing vinyl-containing pyridine monomers with natural rubber latex, pyridine groups can be connected to the dry rubber molecular chains in the latex, and the pyridine groups help to improve the connection strength inside the carbon black masterbatch, and promote the improvement of the hardness and tensile stress of the rubber products containing the carbon black masterbatch; by mixing maleic anhydride with the carbon black solution, carboxyl groups can be connected to the surface of the carbon black, and the carboxyl groups can form hydrogen bonds with the N atoms in the pyridine groups. The force of the hydrogen bonds helps to improve the hardness and tensile stress of the rubber products containing the carbon black masterbatch; and when the modified carbon black slurry is mixed with the During the mixing process of the modified latex, coordination bonds are formed between the pyridine group, oxygen-containing functional groups and metal ions. The synergistic effect of the coordination bonds and hydrogen bonds further enhances the interaction between the carbon black in the carbon black masterbatch and the dry rubber in the latex, improves the connection strength inside the carbon black masterbatch, and improves the hardness and tensile stress of rubber products containing the carbon black masterbatch. In addition, the carboxyl group on the surface of carbon black can play the role of a latex flocculant, allowing the carbon black and latex to combine more fully and completely, thereby improving the dispersion of carbon black and the yield of carbon black masterbatch. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0033] Figure 1 The synthetic route of the modified latex is shown in FIG.

[0034] Figure 2 Schematic diagram of the structure of the prepared modified carbon black (CB represents carbon black);

[0035] Figure 3 Schematic diagram of the interaction between metal ions, modified carbon black and modified latex in carbon black masterbatch. DETAILED DESCRIPTION

[0036] The present application is further described in detail with reference to the following examples. It should be noted that if no specific conditions are specified in the following examples, the conventional conditions or the conditions recommended by the manufacturer are followed, and the raw materials used in the following examples can be obtained from common commercial sources unless otherwise specified.

[0037] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0038] In this application, "first aspect", "second aspect", "third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0039] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0040] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0041] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0042] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by technicians in the technical field of this application. The terms used in this application and in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more related listed items. The term "multiple" in this application means at least two, such as two, three, etc., unless otherwise clearly and specifically limited.

[0043] In the present application, the wet mixing preparation method of carbon black masterbatch comprises:

[0044] (1) Mix natural rubber latex, initiator and vinyl-containing pyridine monomer, stir and obtain modified latex. Figure 1 shown.

[0045] Specifically, when the solid content of natural latex is 50% to 60%, the amount of natural latex used is 160 to 200 parts by weight, the amount of initiator used is 1 to 10 parts; the amount of vinyl-containing pyridine monomer added is 1 to 20 parts. The mixing temperature in the process is 30 to 100°C, the mixing time is 2 to 8 hours, and the stirring speed can be 200 to 1000 rpm. The initiator includes at least one of dibenzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), tert-butyl hydroperoxide (t-BHP), isopropylbenzene hydroperoxide (CHP), diisopropylbenzene peroxide (DCP), potassium persulfate, ammonium persulfate and hydrogen peroxide. The vinyl-containing pyridine monomer includes at least one of 2-vinyl pyridine, 4-vinyl pyridine, 2-methyl-5-enyl pyridine, 2-allyl pyridine and 2-(3-butenyl) pyridine. Preferably, in the above process, the mixing temperature is 80°C, the mixing time is 4 hours, the amount of natural latex with a solid content of 60% is 166 parts by weight, the amount of vinyl-containing pyridine monomer is 25 parts, and the amount of initiator is 3 parts. It can be understood that the dry rubber in the modified latex is a modified dry rubber.

[0046] (2) Mixing maleic anhydride and carbon black solution to obtain modified carbon black slurry.

[0047] Specifically, in this step, the carbon black solution is a mixed solution of carbon black and water with a solid content of 1% to 10%, preferably, the carbon black solution is a mixed solution with a solid content of 4%. The mass ratio of carbon black to maleic anhydride in the carbon black solution is 100:0.1 to 30. The mixing time in this step is 10 min to 60 min, the mixing temperature is 10° C. to 100° C., and during the mixing process, stirring can be performed at a stirring speed of 0 to 4000 rpm.

[0048] It can be understood that the carbon black in the modified carbon black slurry is modified carbon black. The schematic diagram of the modified carbon black is as shown in Figure 2 As shown, wherein CB represents carbon black.

[0049] (3) The modified carbon black slurry is mixed with the modified latex and subjected to coagulation and co-precipitation, and a compound containing metal ions is added during the process to obtain a primary product; the metal ions are used to construct metal coordination bonds, and the primary product is washed and dried to obtain a carbon black masterbatch.

[0050] Specifically, the metal ion is a metal ion with an empty orbital or a lone electron pair, including but not limited to Zn 2 + , Fe 3+ Or Ga 2+ As an example, the compound containing metal ions is zinc chloride, and the mass ratio of zinc chloride to dry rubber in natural rubber latex is 0.1 to 20:100.

[0051] The initial product can be dried at a temperature of 30 to 110°C.

[0052] The schematic diagram of the interaction between metal ions, modified carbon black and modified latex in carbon black masterbatch is as follows: Figure 3 As shown, hydrogen bonds can be formed between the carboxyl groups on the surface of carbon black and the N atoms in the pyridine groups on the dry rubber molecular chains in the natural rubber latex, and the pyridine groups on the dry rubber molecular chains in the latex and the oxygen-containing functional groups on the surface of carbon black can work together with the metal ions to form coordination bonds, which helps to increase the degree of cross-linking between carbon black and the dry rubber in the latex and enhance the interaction force.

[0053] It is understandable that, in the wet mixing process of the carbon black masterbatch, the value can be selected within the above range according to the actual situation. The present application does not specifically limit the order between step (1) and step (2). In other words, step (1) can be performed first, or step (2) can be performed first.

[0054] It should be noted that zinc oxide, stearic acid, antioxidant, accelerator and sulfur can also be mixed with the prepared carbon black masterbatch for kneading, the kneading temperature is 30-150°C, the kneading pressure is 0-0.8MPa, and the kneading time is 10-40min; then vulcanization is carried out in a vulcanizing bed or a flat vulcanizing press, the vulcanization temperature can be 140-160°C, the vulcanization pressure can be 3.5-7.0MPa, and the vulcanization time can be 0.15-1.0h to obtain rubber products (referred to as vulcanized rubber for short), which can be used to prepare products such as tires, V-belts, conveyor belts or hoses.

[0055] Example 1

[0056] 1. The preparation method of carbon black masterbatch is as follows:

[0057] (1) 166 g of natural latex with a solid content of 60%, 25 g of 4-vinylpyridine and 3 g of dibenzoyl peroxide were added into a reactor and mixed, and a stirrer was started to slowly stir at 80° C. for 4 hours to allow the reaction to fully occur, thereby obtaining a modified latex;

[0058] (2) 100 g of carbon black was mixed with water to prepare a carbon black solution with a solid content of 4%, and the mixture was stirred evenly with a stirrer at a speed of 300 rpm for 30 min. During the stirring process, 15 g of maleic anhydride was added and mixed with the carbon black solution and stirred thoroughly to mix evenly. The mixture was then emulsified in a colloid mill at a temperature of 60° C. and a speed of 4000 rpm for 30 min to obtain a modified carbon black slurry.

[0059] (3) Based on 100 g of dry rubber in natural rubber latex and 50 g of carbon black, the corresponding amount of modified carbon black slurry and modified latex were mixed in a composite reactor, and coagulated and precipitated by high-speed stirring. During the stirring process, 10 g of zinc chloride (ZnCl 2 ) to obtain a primary product; after the primary product is washed, it is dried in a forced air drying oven at 80°C to obtain a carbon black masterbatch.

[0060] 2. Preparation of rubber products (hereinafter referred to as vulcanized rubber):

[0061] 5g of zinc oxide, 2g of stearic acid, 1g of antioxidant 4020, 1.2g of accelerator CZ, 2g of sulfur and the prepared carbon black masterbatch were mixed and then refined. After standing for 8 hours, the mixture was vulcanized at 150°C to obtain a vulcanized rubber.

[0062] Example 2

[0063] The specific operation steps are the same as those in Example 1, except that the amount of 4-vinylpyridine used is 5 g.

[0064] Example 3

[0065] The specific operation steps are the same as those in Example 1, except that the amount of 4-vinylpyridine used is 15 g.

[0066] Example 4

[0067] The specific operation steps are the same as those in Example 1, except that the amount of maleic anhydride used is 10 g.

[0068] Example 5

[0069] The specific operation steps are the same as those in Example 1, except that the amount of maleic anhydride used is 20 g.

[0070] Example 6

[0071] The specific operation steps are the same as those in Example 1, except that ZnCl 2 The dosage is 5g.

[0072] Example 7

[0073] The specific operation steps are the same as those in Example 1, except that ZnCl 2 The dosage is 15g.

[0074] Comparative Example 1

[0075] 1. Preparation of carbon black masterbatch

[0076] 50g of carbon black was mixed with 1200g of water to prepare a carbon black solution with a solid content of 4%, and the mixture was stirred in a stirrer to obtain a carbon black suspension. The stirrer speed was 300rpm and the stirring time was 30min. The carbon black suspension was then added to a colloid mill for grinding. The colloid mill speed was 4000r / min, the grinding time was 30min, and the temperature was 60°C. The carbon black slurry and 166g of natural latex with a solid content of 60% were coagulated and precipitated in a composite reactor under high-speed stirring, and then washed and dried at 80°C in a forced air drying oven to obtain a carbon black masterbatch.

[0077] 2. Preparation of vulcanized rubber:

[0078] 5g of zinc oxide, 2g of stearic acid, 1g of antioxidant 4020, 1.2g of accelerator CZ, 2g of sulfur and the prepared carbon black masterbatch were mixed and then refined. After standing for 8 hours, the mixture was vulcanized at 150°C to obtain a vulcanized rubber.

[0079] Comparative Example 2

[0080] The specific operation steps are the same as those in Example 1, except that step (1) is not performed, and in step (3), 166 g of natural latex with a solid content of 60% is mixed with the modified carbon black slurry in a composite reactor before the subsequent steps are performed.

[0081] Comparative Example 3

[0082] The specific operation steps are the same as those in Example 1, except that step (2) is not performed. In step (3), the modified latex and 150 g of carbon black are mixed with 1200 g of water to prepare a carbon black solution with a solid content of 4%, which is mixed in a composite reactor and the subsequent steps are performed.

[0083] Comparative Example 4

[0084] The specific operation steps are the same as those of Example 1, except that 15 g of maleic anhydride in step (2) is added to step (1) to obtain a modified latex; in step (2), the homogenized carbon black solution is emulsified in a colloid mill; in step (3), the emulsified carbon black slurry is mixed with the modified latex in a composite reactor, and subsequent steps are performed.

[0085] Comparative Example 5

[0086] Add 100g natural rubber, 50g carbon black (N234), 5g zinc oxide, 2g stearic acid and 1g antioxidant 4020 in an internal mixer for mixing. After mixing, discharge the rubber. Then add 1.2g accelerator CZ and 2g sulfur on an open mixer. Mix well and produce a sheet. After standing for 8 hours, vulcanize at 150℃ on a flat vulcanizer to obtain a vulcanized rubber.

[0087] Performance testing

[0088] The yields of the carbon black masterbatch obtained in Examples 1-7 and Comparative Examples 1-4 were calculated by the following formula and are listed in Table 1:

[0089] The yield of carbon black masterbatch = the actual mass of carbon black masterbatch / (the mass of carbon black + the mass of dry rubber in natural latex) × 100%;

[0090] According to the method in the national standard "GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", the tensile properties of the vulcanized rubber obtained in Examples 1-7 and Comparative Examples 1-5 were tested. The tensile machine model was AG-20KNG produced by Shimadzu Corporation, and the 100% modulus of tensile stress (MPa) and 300% modulus of tensile stress (MPa) were obtained; according to the national standard "GB / T 531.1-2008 Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore durometer method", the Shore A hardness (unit: Shore A) of the vulcanized rubber obtained in Examples 1-7 and Comparative Examples 1-5 was tested; according to the method in the national standard "Determination of temperature rise and fatigue resistance of vulcanized rubber in flexure test Part 3: Compression flexure test", the compression heat generation (℃) of the vulcanized rubber obtained in Examples 1-7 and Comparative Examples 1-5 was tested. The test results are shown in Table 1.

[0091] Table 1. Performance test data of Examples 1-7 and Comparative Examples 1-5

[0092]

[0093] It can be seen from the data in Table 1 that Comparative Example 1 is a vulcanized rubber obtained by wet mixing of unmodified carbon black and natural rubber latex. Compared with Examples 1-7, the hardness is significantly reduced and is also less than the hardness of the vulcanized rubber obtained by dry mixing in Comparative Example 5; the hardness of the vulcanized rubber obtained in Comparative Examples 2-4 is also less than the hardness of the vulcanized rubber obtained in Examples 1-7, and the reduction in the hardness of the vulcanized rubber is not conducive to the manufacture of tires. Moreover, the 100% tensile stress and 300% tensile stress of the vulcanized rubber prepared in Comparative Examples 1-4 are also smaller than those of the vulcanized rubber prepared in Examples 1-7. This is because in the wet mixing preparation process of Examples 1-7, the natural latex is modified by a vinyl-containing pyridine monomer, a pyridine group is introduced into the dry rubber molecular chain in the natural latex, the carbon black is modified by maleic anhydride, an oxygen-containing functional group carboxyl is introduced into the surface of the carbon black, the pyridine group on the dry rubber molecular chain in the natural latex and the oxygen-containing functional group on the surface of the carbon black form coordination bonds with metal ions, and the pyridine group on the dry rubber molecular chain in the natural latex and the oxygen-containing functional group on the surface of the carbon black can form hydrogen bonds, and the interaction between the coordination bonds and the hydrogen bonds increases the degree of crosslinking between the carbon black and the dry rubber in the natural latex, thereby improving the hardness and tensile stress of the vulcanized rubber prepared by wet mixing. In Comparative Examples 1-4, the carbon black and natural rubber latex were not modified, or only one of the carbon black and natural rubber latex was modified, which could not achieve the above effect and the performance of the obtained vulcanized rubber was poor.

[0094] It should also be noted that in Comparative Example 1, carbon black and natural latex were not modified, and the yield of carbon black masterbatch was only 82.3%. As the amount of maleic anhydride, the modifier, increased, the masterbatch yield increased. The possible reason is that the free carboxyl groups generated by the hydrolysis of maleic anhydride on the surface of carbon black played a role in latex flocculation. Compared with Comparative Examples 1-4, the yield of carbon black masterbatch prepared by the preparation method protected in this application was higher, all above 91%.

[0095] By analyzing the compression heat generation data in Table 1, it can be seen that the compression heat generation of the vulcanized rubbers prepared in Examples 1-7 is greatly reduced compared to Comparative Example 5. This may be due to the formation of metal coordination bonds between the modified natural latex and the modified carbon black and the metal ions, and the synergistic hydrogen bonding to improve the interaction between the carbon black and the dry rubber in the natural latex, improve the dispersion of the carbon black in the dry rubber in the natural latex, and thus improve the hysteresis performance of the vulcanized rubber, thereby reducing the compression heat generation of the vulcanized rubber. The compression heat generation of the vulcanized rubbers prepared in Examples 1-7 is less than the compression heat generation of the vulcanized rubber prepared in Comparative Examples 1-4, which shows that the performance of the carbon black masterbatch prepared by the preparation method to be protected in this application is more excellent.

[0096] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A wet mixing method for preparing carbon black masterbatch, characterized in that: include: Mixing natural rubber latex, an initiator and a vinyl-containing pyridine monomer, stirring, and obtaining a modified latex; mixing maleic anhydride with the carbon black solution to obtain a modified carbon black slurry; The modified carbon black slurry is mixed with the modified latex and then coagulated and precipitated, and a compound containing metal ions is added in the process to obtain a primary product; the metal ions are used to construct metal coordination bonds, and the primary product is washed and dried to obtain the carbon black masterbatch.

2. The wet mixing method for preparing carbon black masterbatch according to claim 1, characterized in that: The preparation process of the modified latex includes at least one of the following features (a)-(d): (a) When the solid content of the natural rubber latex is 50% to 60%, the amount of the natural rubber latex used is 160 to 200 parts by weight, the amount of the initiator used is 1 to 10 parts by weight, and the amount of the vinyl-containing pyridine monomer added is 1 to 20 parts by weight; (b) The mixing temperature is 30 to 100°C and the mixing time is 2 to 8 hours; (c) the initiator comprises at least one of dibenzoyl peroxide, azobisisobutyronitrile, tert-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, potassium persulfate, ammonium persulfate and hydrogen peroxide; (d) The vinyl-containing pyridine monomer includes at least one of 2-vinylpyridine, 4-vinylpyridine, 2-methyl-5-enylpyridine, 2-allylpyridine and 2-(3-butenyl)pyridine.

3. The wet mixing method for preparing carbon black masterbatch according to claim 1, characterized in that: The preparation process of the modified carbon black slurry includes at least one of the following features (e)-(h): (e) The carbon black solution is a mixed solution of carbon black and water with a solid content of 1% to 10%; (f) the mass ratio of carbon black in the carbon black solution to the maleic anhydride is 100:0.1-30; (g) the maleic anhydride and the carbon black solution are mixed for 10 to 60 minutes at a temperature of 10° C. to 100° C.; (h) The maleic anhydride and the carbon black solution are mixed at a stirring speed of 0 to 4000 rpm.

4. The wet mixing method for preparing carbon black masterbatch according to claim 1, characterized in that: The metal ion is Zn 2+ , Fe 3+ Or Ga 2+ .

5. The wet mixing method for preparing carbon black masterbatch according to claim 4, characterized in that: The metal ion-containing compound is zinc chloride.

6. The wet mixing method for preparing carbon black masterbatch according to claim 5, characterized in that: The mass ratio of the zinc chloride to the dry rubber in the natural rubber latex is 0.1 to 20:

100.

7. The wet mixing method for preparing carbon black masterbatch according to any one of claims 1 to 6, characterized in that: The primary product is dried at a temperature of 30-110°C.

8. A carbon black masterbatch, characterized in that: The carbon black masterbatch is prepared by the wet mixing preparation method of any one of claims 1 to 7.

9. A rubber product, characterized in that: The carbon black masterbatch according to claim 8 also comprises zinc oxide, stearic acid, an antioxidant, an accelerator and sulfur.

10. The rubber product according to claim 9, characterized in that Used for preparing tires, V-belts, conveyor belts or hoses.

Citation Information

Patent Citations

  • Preparation method of carbon-black-containing butadiene styrene rubber master batch

    CN104211837A

  • Nano zinc oxide / rubber composite material and preparation method thereof

    CN109749168A